Gen. Math. Notes, Vol. 6, No. 1, September 2011, pp.1-14 ISSN 2219-7184; Copyright c ICSRS Publication, 2011 www.i-csrs.org Available free online at http://www.geman.in Integrals Involving I-Function U.K. Saha1 , L.K. Arora2 and B.K. Dutta3 1 Department of Mathematics North Eastern Regional Institute of Science and Technology Nirjuli-791109, Arunachal Pradesh, India E-mail: uksahanerist@gmail.com 2 Department of Mathematics North Eastern Regional Institute of Science and Technology Nirjuli-791109, Arunachal Pradesh, India E-mail: lkarora nerist@yahoo.com 3 Department of Mathematics North Eastern Regional Institute of Science and Technology Nirjuli-791 109, Arunachal Pradesh, India E-mail: dutta.bk08@yahoo.com (Received:11-4-11 /Accepted:10-7-11) Abstract In this paper, we have presented certain integrals involving product of the Ifunction with exponential function, Gauss’s hypergeometric function and Fox’s H-function. The results derived here are basic in nature and may include a number of known and new results as particular cases. Keywords: Exponential function, hypergeometric function, H-function, I-function, Mellin-Barnes type contour integral. 1 Introduction The Gaussian hypergeometric function is of fundamental importance in the theory of special functions. The importance of this function lies in the fact that almost all of the commonly used functions of applicable mathematics, mathematical physics, engineering and mathematical biology are expressible as its special cases. 2 U.K. Saha et al. The series 2 F1 (a, b; c; z) = ∞ X (a)n (b)n z n n=0 (c)n n! , (1) where (a)n is the Pochhammer symbol defined by (a)n = a(a + 1) . . . (a + n − 1), n ∈ N 1, n=0 (2) is called the Gauss’s hypergeometric series after the famous German mathematician Carl Friedrich Gauss (1777-1855) who in the year 1812 introduced this series. It is represented by the symbol 2 F1 (a, b; c; z) and is called the Gauss’s hypergeometric function also. In 1961, Charles Fox [2] introduced a function which is more general than the Meijer’s G-function and this function is well known in the literature of special functions as Fox’s H-function or simply the H-function. This function is defined and represented by means of the following Mellin-Barnes type contour integral: Z 1 (aj , αj )1,p m,n m,n θ(s)z s ds, (3) H[z] = Hp,q [z] = Hp,q z = (bj , βj )1,q 2πi L where, for convenience, Qn Qm j=1 Γ(1 − aj + αj s) j=1 Γ(bj − βj s) Qp , θ(s) = Qq j=n+1 Γ(aj − αj s) j=m+1 Γ(1 − bj + βj s) (4) and L is a suitable contour of the Mellin-Barnes type which runs from −i∞ to +i∞, separating the poles of Γ(bj − βj s), j = 1, . . . , m from those of Γ(1 − aj + αj s), j = 1, . . . , n. An empty product is interpreted as unity. The integers m, n, p, q satisfy the inequalities 0 ≤ n ≤ p, 0 ≤ m ≤ q; the coefficients αj (j = 1, . . . , p), βj (j = 1, . . . , q) are positive real numbers, and the complex parameters aj (j = 1, . . . , p), bj (j = 1, . . . , q) are so constrained that no poles of the integrand coincide. Owing to the popularity of the special functions, those are defined in (1) and (3) (c.f. [4], [3] and [6]), details regarding these are avoided. The I-function, which is more general than the Fox’s H-function, defined by V.P. Saxena [5], by means of the following Mellin-Barnes type contour integral: Z 1 (aj , αj )1,n ; (aji , αji )n+1,pi m,n m,n I[z] = Ipi ,qi :r [z] = Ipi ,qi :r z = φ(ξ)z ξ dξ, (bj , βj )1,m ; (bji , βji )m+1,qi 2πi L (5) 3 Integrals Involving I-Function where, Qm φ(ξ) = Σri=1 nQ Γ(bj − βj ξ) Qn Γ(1 − aj + αj ξ) o, Qpi qi Γ(1 − b + β ξ) Γ(a − α ξ) ji ji ji ji j=m+1 j=n+1 j=1 j=1 (6) pi , qi (i = 1, . . . , r), m, n are integers satisfying 0 ≤ n ≤ pi , 0 ≤ m ≤ qi ; αj , βj , αji , βji are real and positive and aj , bj , aji , bji are complex numbers. L is a suitable contour of the Mellin-Barnes type running from γ − iα to γ + iα (γ is real) in the complex ξ-plane. Details regarding existence conditions and various parametric restrictions of I-function, we may refer [5]. For r = 1, (5) reduces to the Fox’s H-function (aj , αj )1,n ; (aji , αji )n+1,pi (aj , αj )1,n ; (aj , αj )n+1,p m,n m,n Ipi ,qi :1 z = Hp,q z (bj , βj )1,m ; (bji , βji )m+1,qi (bj , βj )1,m ; (bj , βj )m+1,q 2 Required Results We shall require the following results in the sequel: The Mellin transform of the H-function follows from the definition (3) in view of the well-known Mellin inversion theorem. We have " # Z ∞ (a , α ) j j 1,p m,n xs−1 Hp,q ax dx = a−s θ(−s) (b , β ) j j 1,q 0 Qn Qm j=1 Γ(1 − aj − αj s) j=1 Γ(bj + βj s) −s Qp , (7) = a Qq j=n+1 Γ(aj + αj s) j=m+1 Γ(1 − bj − βj s) where, A= n X αj − j=1 p X αj + j=n+1 m X q X βj − j=1 j=m+1 q p βj > 0, X X 1 | arg a| < Aπ, δ = βj − αj > 0 2 j=1 j=1 and − min [Re(bj /βj )] < Re(s) < min [Re{(1 − aj )/αj }]. 1≤j≤m 1≤j≤n Lemma 2.1 From Rainville [4], we have ∞ X ∞ X n=0 k=0 A(k, n) = ∞ X n X n=0 k=0 A(k, n − k) (8) 4 U.K. Saha et al. 3 Main Results In this section, we have evaluated certain integrals involving product of the Ifunction with exponential function, Gauss’s hypergeometric function and Fox’s H-function. First Integral Z t xρ−1 (t − x)σ−1 e−xz 2 F1 (α, β; γ; axζ (t − x)η ) 0 m,n µ ν (aj , αj )1,n ; (aji , αji )n+1,pi × Ipi ,qi :r yx (t − x) dx (bj , βj )1,m ; (bji , βji )m+1,qi ∞ X n X z u−k (ζ+η−1)k+u −zt ρ+σ−1 =e t f (k) t (u − k)! u=0 k=0 (1 − ρ − ζk, µ), (1 − σ − (η − 1)k − u, ν), m,n+2 × Ipi +2,qi +1:r ytµ+ν (bj , βj )1,m ; (bji , βji )m+1,qi , I1 ≡ (aj , αj )1,n ; (aji , αji )n+1,pi , (1 − ρ − σ − (ζ + η − 1)k − u, µ + ν) (9) where, f (k) = (α)k (β)k ak , (γ)k k! provided (i) µ ≥ 0, ν ≥ 0 (not both zero simultaneously) (ii) ζ and η are non-negative integers such that ζ + η ≥ 1 1 (iii) Ai > 0, ∀i ∈ 1, . . .P , r; where i < 0; | arg PB Ppiy| < 2 Ai π,P n qi Ai = j=1 αj − j=n+1 αji + m β − j=1 j j=m+1 βji , P P qi pi 1 Bi = 2 (pi − qi ) + j=1 bji − j=1 aji (iv) Re(ρ) + µ min1≤j≤m [Re(bj /βj )] > 0, Re(σ) + ν min1≤j≤m [Re(bj /βj )] > 0. Proof: −zt Z t xρ−1 (t − x)σ−1 e(t−x)z 2 F1 (α, β; γ; axζ (t − x)η ) 0 µ ν (aj , αj )1,n ; (aji , αji )n+1,pi m,n × Ipi ,qi :r yx (t − x) dx (bj , βj )1,m ; (bji , βji )m+1,qi I1 ≡ e (10) 5 Integrals Involving I-Function P (t−x)u z u Now we replace e(t−x)z by ∞ and express the hypergeometric funcu=0 u! tion and the I-function with the help of (1) and (5) respectively, to get I1 = e −zt t Z x ρ−1 σ−1 (t − x) 0 ∞ ∞ X (t − x)u z u X (α)k (β)k ak xζk (t − x)ηk u! (γ)k k! u=0 k=0 Z 1 × φ(ξ)y ξ xµξ (t − x)νξ dξdx 2πi L Z t ∞ X ∞ X (α)k (β)k ak xζk (t − x)ηk+u z u ρ−1 σ−1 −zt x (t − x) =e (γ)k k! u! 0 u=0 k=0 Z 1 × φ(ξ)y ξ xµξ (t − x)νξ dξdx 2πi L Now by the use of (8), the above result reduces to −zt Z t I1 = e x ρ−1 σ−1 (t − x) 0 1 × 2πi Z ∞ X n X (α)k (β)k ak xζk (t − x)ηk+u−k z u−k (γ)k k! (u − k)! u=0 k=0 φ(ξ)y ξ xµξ (t − x)νξ dξdx L Interchanging the order of integration and summation, we obtain −zt I1 = e ∞ X n X u=0 t z u−k 1 f (k) (u − k)! 2πi k=0 Z × x ρ+ζk+µξ−1 Z φ(ξ)y ξ L σ+(η−1)k+u+νξ−1 (t − x) dx dξ, 0 where f (k) is given by (10). On substituting x = ts in the inner x-integral, the above expression reduces to n ∞ X X Z z u−k (ζ+η−1)k+u 1 I1 = e t f (k) t φ(ξ)y ξ t(µ+ν)ξ (u − k)! 2πi L u=0 k=0 Z 1 × sρ+ζk+µξ−1 (1 − s)σ+(η−1)k+u+νξ−1 ds dξ −zt ρ+σ−1 0 −zt ρ+σ−1 =e t n ∞ X X u=0 z u−k (ζ+η−1)k+u 1 f (k) t (u − k)! 2πi k=0 Z φ(ξ) L Γ(ρ + ζk + µξ)Γ(σ + (η − 1)k + u + νξ) ξ (µ+ν)ξ × y t dξ Γ(ρ + σ + (ζ + η − 1)k + u + (µ + ν)ξ) 6 U.K. Saha et al. Finally, interpreting the contour integral by virtue of (5), we obtain −zt ρ+σ−1 I1 = e t ∞ X n X f (k) u=0 k=0 × z u−k (ζ+η−1)k+u t (u − k)! (1 − ρ − ζk, µ), (1 − σ − (η − 1)k − u, ν), (bj , βj )1,m ; (bji , βji )m+1,qi , (aj , αj )1,n ; (aji , αji )n+1,pi . (1 − ρ − σ − (ζ + η − 1)k − u, µ + ν) Ipm,n+2 i +2,qi +1:r ytµ+ν Second Integral Z t I2 ≡ xρ−1 (t − x)σ−1 e−xz 2 F1 (α, β; γ; axζ (t − x)η ) 0 m,n −µ −ν (aj , αj )1,n ; (aji , αji )n+1,pi dx × Ipi ,qi :r yx (t − x) (bj , βj )1,m ; (bji , βji )m+1,qi ∞ X n X z u−k (ζ+η−1)k+u = e−zt tρ+σ−1 f (k) t (u − k)! u=0 k=0 (aj , αj )1,n ; (aji , αji )n+1,pi , m+2,n × Ipi +1,qi +2:r yt−µ−ν (ρ + ζk, µ), (σ + (η − 1)k + u, ν), (ρ + σ + (ζ + η − 1)k + u, µ + ν) , (bj , βj )1,m ; (bji , βji )m+1,qi (11) provided Re(ρ) − µ max [Re{(aj − 1)/αj }] > 0, 1≤j≤n Re(σ) − ν max [Re{(aj − 1)/αj }] > 0, 1≤j≤n along with the sets of conditions (i) to (iii) given with I1 and f (k) is given by (10). Third Integral Z t I3 ≡ xρ−1 (t − x)σ−1 e−xz 2 F1 (α, β; γ; axζ (t − x)η ) 0 µ −ν (aj , αj )1,n ; (aji , αji )n+1,pi m,n dx × Ipi ,qi :r yx (t − x) (bj , βj )1,m ; (bji , βji )m+1,qi ∞ X n X z u−k (ζ+η−1)k+u −zt ρ+σ−1 t =e t f (k) (u − k)! u=0 k=0 (1 − ρ − ζk, µ), m+1,n+1 × Ipi +1,qi +2:r ytµ−ν (σ + (η − 1)k + u, ν), (bj , βj )1,m ; 7 Integrals Involving I-Function (aj , αj )1,n ; (aji , αji )n+1,pi , (bji , βji )m+1,qi , (1 − ρ − σ − (ζ + η − 1)k − u, µ − ν) (12) provided µ > 0, ν ≥ 0 such that µ − ν ≥ 0, Re(ρ) + µ min [Re(bj /βj )] > 0, 1≤j≤m Re(σ) − ν max [Re{(aj − 1)/αj }] > 0, 1≤j≤n along with the sets of conditions (i) to (iii) given with I1 and f (k) is given by (10). Fourth Integral Z t xρ−1 (t − x)σ−1 e−xz 2 F1 (α, β; γ; axζ (t − x)η ) I4 ≡ 0 m,n µ −ν (aj , αj )1,n ; (aji , αji )n+1,pi × Ipi ,qi :r yx (t − x) dx (bj , βj )1,m ; (bji , βji )m+1,qi ∞ X n X z u−k (ζ+η−1)k+u t = e−zt tρ+σ−1 f (k) (u − k)! u=0 k=0 (1 − ρ − ζk, µ), (aj , αj )1,n ; m+1,n+1 × Ipi +2,qi +1:r ytµ−ν (σ + (η − 1)k + u, ν), (aji , αji )n+1,pi , (ρ + σ + (ζ + η − 1)k + u, ν − µ) , (bj , βj )1,m ; (bji , βji )m+1,qi (13) provided µ ≥ 0, ν > 0 such that ν − µ ≥ 0, Re(ρ) − µ max [Re{(aj − 1)/αj }] > 0, 1≤j≤n Re(σ) + ν min [Re(bj /βj )] > 0, 1≤j≤m along with the sets of conditions (i) to (iii) given with I1 and f (k) is given by (10). Fifth Integral Z t I5 ≡ xρ−1 (t − x)σ−1 e−xz 2 F1 (α, β; γ; axζ (t − x)η ) 0 m,n −µ ν (aj , αj )1,n ; (aji , αji )n+1,pi dx × Ipi ,qi :r yx (t − x) (bj , βj )1,m ; (bji , βji )m+1,qi ∞ X n X z u−k (ζ+η−1)k+u −zt ρ+σ−1 =e t f (k) t (u − k)! u=0 k=0 (1 − σ − (η − 1)k − u, ν), (aj , αj )1,n ; m+1,n+1 × Ipi +2,qi +1:r yt−µ+ν (ρ + ζk, µ), 8 U.K. Saha et al. (aji , αji )n+1,pi , (ρ + σ + (ζ + η − 1)k + u, µ − ν) , (bj , βj )1,m ; (bji , βji )m+1,qi (14) provided µ > 0, ν ≥ 0 such that µ − ν ≥ 0, Re(ρ) + µ min [Re(bj /βj )] > 0, 1≤j≤m Re(σ) − ν max [Re{(aj − 1)/αj }] > 0, 1≤j≤n along with the sets of conditions (i) to (iii) given with I1 and f (k) is given by (10). Sixth Integral Z t xρ−1 (t − x)σ−1 e−xz 2 F1 (α, β; γ; axζ (t − x)η ) 0 m,n −µ ν (aj , αj )1,n ; (aji , αji )n+1,pi × Ipi ,qi :r yx (t − x) dx (bj , βj )1,m ; (bji , βji )m+1,qi ∞ X n X z u−k (ζ+η−1)k+u −zt ρ+σ−1 t =e t f (k) (u − k)! u=0 k=0 (1 − σ − (η − 1)k − u, ν), (aj , αj )1,n ; m+1,n+1 × Ipi +1,qi +2:r yt−µ+ν (ρ + ζk, µ), (bj , βj )1,m ; (bji , βji )m+1,qi , I6 ≡ (aji , αji )n+1,pi , (1 − ρ − σ − (ζ + η − 1)k − u, ν − µ) (15) provided µ ≥ 0, ν > 0 such that ν − µ ≥ 0, Re(ρ) − µ max [Re{(aj − 1)/αj }] > 0, 1≤j≤n Re(σ) + ν min [Re(bj /βj )] > 0, 1≤j≤m along with the sets of conditions (i) to (iii) given with I1 and f (k) is given by (10). The integrals (11) to (15) can be proved on lines similar to those of integral (9). 9 Integrals Involving I-Function Seventh Integral Z ∞ σ (aj , αj )1,n1 ; (aji , αji )n1 +1,pi η−1 ax ρ m1 ,n1 I7 ≡ x e 2 F1 (α, β; γ; ax )Ipi ,qi :r zx (bj , βj )1,m1 ; (bji , βji )m1 +1,qi 0 (cj , γj )1,n ; (cj , γj )n+1,p m,n wx dx × Hp,q (dj , δj )1,m ; (dj , δj )m+1,q ∞ X n X au−k −η =w f (k) w−(ρ−1)k−u (u − k)! u=0 k=0 (aj , αj )1,n1 , (1 − dj − (η + (ρ − 1)k + u)δj , σδj )1,m ; m1 +n,n1 +m × Ipi +q,qi +p:r zw−σ (bj , βj )1,m1 , (1 − cj − (η + (ρ − 1)k + u)γj , σγj )1,n ; (aji , αji )n1 +1,pi , (1 − dj − (η + (ρ − 1)k + u)δj , σδj )m+1,q (bji , βji )m1 +1,qi , (1 − cj − (η + (ρ − 1)k + u)γj , σγj )n+1,p , (16) where, (α)k (β)k ak , f (k) = (γ)k k! (17) provided (i) λ > 0, | arg z| < 12 πλ (ii) λ ≥ 0, | arg z| ≤ 12 πλ, Re(µ + 1) < 0 (iii) λ1 > 0, | arg w| < 12 πλ1 (iv) λ1 ≥ 0, | arg w| ≤ 12 πλ1 , Re(µ1 + 1) < 0 (v) σ > 0, −σ min1≤j≤m1 [Re(bj /βj )] − min1≤j≤m [Re(dj /δj )] < Re(η) < σ < min1≤j≤n1 [Re{(1 − aj )/αj }] + min1≤j≤n [Re{(1 − cj )/γj }] and where, λ= µ= λ1 = n1 X αj + m1 X j=1 j=1 m1 X n1 X j=1 m X j=1 bj − δj + j=1 n X pi X " βj − max 1≤i≤r j=n1 +1 1≤i≤r X γj − j=1 q X j=m+1 p aji − j=n1 +1 q X X 1 µ1 = (p − q) + dj − cj 2 j=1 j=1 qi X j=m1 +1 p δj − X j=n+1 # βji j=m1 +1 pi " aj − min αji + qi X γj bji + pi q i − 2 2 # 10 U.K. Saha et al. P∞ au xu Proof: We replace eax by and express the hypergeometric u=0 u! function and the I-function with the help of (1) and (5) respectively, to obtain Z ∞ Z ∞ ∞ X au xu X (α)k (β)k ak xρk 1 η−1 x I7 = φ(ξ)z ξ xσξ u! (γ) k! 2πi k 0 L u=0 k=0 (cj , γj )1,n ; (cj , γj )n+1,p m,n × Hp,q wx dξdx (dj , δj )1,m ; (dj , δj )m+1,q Z ∞ Z ∞ X ∞ X (α)k (β)k ak xρk+u au 1 η−1 x = φ(ξ)z ξ xσξ (γ) k! u! 2πi k 0 L u=0 k=0 (cj , γj )1,n ; (cj , γj )n+1,p m,n × Hp,q wx dξdx (dj , δj )1,m ; (dj , δj )m+1,q Now by the use of (8), the above result reduces to Z Z ∞ ∞ X n X (α)k (β)k ak xρk+u−k au−k 1 η−1 φ(ξ)z ξ xσξ x I7 = (γ) k! (u − k)! 2πi k L 0 u=0 k=0 (cj , γj )1,n ; (cj , γj )n+1,p m,n × Hp,q wx dξdx (dj , δj )1,m ; (dj , δj )m+1,q Interchanging the order of integration and summation, we obtain Z ∞ Z ∞ X n X au−k 1 ξ f (k) I7 = φ(ξ)z xη+(ρ−1)k+u+σξ−1 (u − k)! 2πi L 0 u=0 k=0 (cj , γj )1,n ; (cj , γj )n+1,p m,n × Hp,q wx dx dξ, (dj , δj )1,m ; (dj , δj )m+1,q where f (k) is given by (17). Now we use the Mellin transform of H-function by virtue of (7), so that Z ∞ X n X au−k 1 φ(ξ)z ξ w−(η+(ρ−1)k+u+σξ) I7 = f (k) (u − k)! 2πi L u=0 k=0 Qm j=1 Γ(dj + δj (η + (ρ − 1)k + u + σξ)) × Qq Γ(1 − dj − δj (η + (ρ − 1)k + u + σξ)) Qj=m+1 n j=1 Γ(1 − cj − γj (η + (ρ − 1)k + u + σξ)) × Qp dξ j=n+1 Γ(cj + γj (η + (ρ − 1)k + u + σξ)) Z ∞ X n X au−k −η −(ρ−1)k−u 1 = w f (k) w φ(ξ) (u − k)! 2πi L u=0 k=0 Qm j=1 Γ(dj + (η + (ρ − 1)k + u)δj + σδj ξ)) × Qq Γ(1 − dj − (η + (ρ − 1)k + u)δj − σδj ξ)) Qj=m+1 n j=1 Γ(1 − cj − (η + (ρ − 1)k + u)γj − σγj ξ)) ξ −σξ × Qp z w dξ j=n+1 Γ(cj + (η + (ρ − 1)k + u)γj + σγj ξ)) 11 Integrals Involving I-Function Finally, interpreting the contour integral by virtue of (5), we obtain I7 =w −η ∞ X n X f (k) u=0 k=0 × 1 +n,n1 +m Ipmi +q,q i +p:r au−k w−(ρ−1)k−u (u − k)! (aj , αj )1,n1 , (1 − dj − (η + (ρ − 1)k + u)δj , σδj )1,m ; zw−σ (bj , βj )1,m1 , (1 − cj − (η + (ρ − 1)k + u)γj , σγj )1,n ; (aji , αji )n1 +1,pi , (1 − dj − (η + (ρ − 1)k + u)δj , σδj )m+1,q (bji , βji )m1 +1,qi , (1 − cj − (η + (ρ − 1)k + u)γj , σγj )n+1,p 4 . Particular Cases Putting r = 1, t = 1 and η = 0 in (9), (11), (12), (13), (14) and (15) the following known as well as new results may be realised: (i) Integral (9) leads to the known result [1, p. 246, eq. (2.2)]: Z 1 ρ−1 σ−1 −xz ζ m,n µ ν (aj , αj )1,p x (1 − x) e 2 F1 (α, β; γ; ax )Hp,q yx (1 − x) dx (bj , βj )1,q 0 ∞ X n X z u−k (1 − ρ − ζk, µ), m,n+2 −z =e f (k) H y (bj , βj )1,q , (u − k)! p+2,q+1 u=0 k=0 (1 − σ + k − u, ν), (aj , αj )1,p , (1 − ρ − σ − (ζ − 1)k − u, µ + ν) (18) where, f (k) = (α)k (β)k ak . (γ)k k! (ii) Integral (11) leads to the another known result [1, p. 248, eq. (3.1)]: Z 1 ζ m,n −µ −ν (aj , αj )1,p ρ−1 σ−1 −xz x (1 − x) e 2 F1 (α, β; γ; ax )Hp,q yx (1 − x) dx (bj , βj )1,q 0 ∞ X n X z u−k (aj , αj )1,p , m+2,n −z f (k) =e Hp+1,q+2 y (ρ + ζk, µ), (u − k)! u=0 k=0 (ρ + σ + (ζ − 1)k + u, µ + ν) , (σ − k + u, ν), (bj , βj )1,q where, f (k) = (α)k (β)k ak . (γ)k k! (19) 12 U.K. Saha et al. (iii) Integral (12) reduces to the known result [1, p. 248, eq. (3.2)]: Z 1 x ρ−1 (1 − x) σ−1 −xz e 2 F1 (α, β; γ; ax ζ m,n )Hp,q µ −ν yx (1 − x) 0 =e −z (aj , αj )1,p (bj , βj )1,q dx ∞ X n X u=0 z u−k (1 − ρ − ζk, µ), m+1,n+1 f (k) Hp+1,q+2 y (σ − k + u, ν), (bj , βj )1,q , (u − k)! k=0 (aj , αj )1,p , (1 − ρ − σ − (ζ − 1)k − u, µ − ν) (20) where, f (k) = (α)k (β)k ak . (γ)k k! (iv) Integral (13) leads to the known result [1, p. 249, eq. (3.3)]: Z 1 x ρ−1 (1 − x) σ−1 −xz e 2 F1 (α, β; γ; ax ζ m,n )Hp,q µ −ν yx (1 − x) 0 =e −z (aj , αj )1,p (bj , βj )1,q dx ∞ X n X u=0 z u−k (1 − ρ − ζk, µ), (aj , αj )1,p , m+1,n+1 Hp+2,q+1 y f (k) (σ − k + u, ν), (u − k)! k=0 (ρ + σ + (ζ − 1)k + u, ν − µ) , (bj , βj )1,q (21) where, f (k) = (α)k (β)k ak . (γ)k k! (v) Integral (14) reduces to the result: Z 1 x ρ−1 (1 − x) σ−1 −xz e 2 F1 (α, β; γ; ax ζ m,n )Hp,q yx 0 =e −z −µ ν (1 − x) (aj , αj )1,p (bj , βj )1,q dx ∞ X n X u=0 z u−k (1 − σ + k − u, ν), (aj , αj )1,p , m+1,n+1 f (k) Hp+2,q+1 y (ρ + ζk, µ), (u − k)! k=0 (ρ + σ + (ζ − 1)k + u, µ − ν) , (bj , βj )1,q where, f (k) = (α)k (β)k ak . (γ)k k! (22) 13 Integrals Involving I-Function (vi) Integral (15) leads to the result: Z 1 x ρ−1 (1 − x) σ−1 −xz e 2 F1 (α, β; γ; ax ζ m,n )Hp,q −µ yx ν (1 − x) 0 =e −z (aj , αj )1,p (bj , βj )1,q dx ∞ X n X u=0 z u−k (1 − σ + k − u, ν), m+1,n+1 f (k) Hp+1,q+2 y (ρ + ζk, µ), (bj , βj )1,q , (u − k)! k=0 (aj , αj )1,p , (1 − ρ − σ − (ζ − 1)k − u, ν − µ) (23) where, f (k) = (α)k (β)k ak . (γ)k k! (vii) Putting a = 0 in (16), the exponential function eax and the hypergeometric function reduces to unity and consequently it leads to a result by V.P. Saxena [5, p. 66, eq. (4.5.1)]: ∞ (aj , αj )1,n ; (aji , αji )n+1,pi zx (bj , βj )1,m ; (bji , βji )m+1,qi 0 (cj , γj )1,n ; (cj , γj )n+1,p m,n × Hp,q wx dx (dj , δj )1,m ; (dj , δj )m+1,q (aj , αj )1,n1 , (1 − dj − ηδj , σδj )1,m ; −η m1 +n,n1 +m =w Ipi +q,qi +p:r zw−σ (bj , βj )1,m1 , (1 − cj − ηγj , σγj )1,n ; Z 1 xη−1 Ipmi ,q1 ,n i :r σ (aji , αji )n1 +1,pi , (1 − dj − ηδj , σδj )m+1,q (bji , βji )m1 +1,qi , (1 − cj − ηγj , σγj )n+1,p 5 . (24) Conclusion The I-function, presented in this paper, is quite basic in nature. Therefore, on specializing the parameters of this function, we may obtain various other special functions such as Fox’s H-function, Meijer’s G-function, Wright’s generalized Bessel function, Wright’s generalized hypergeometric function, MacRobert’s E-function, generalized hypergeometric function, Bessel function of first kind, modified Bessel function, Whittaker function, exponential function, binomial function etc. as its special cases, and therefore, various unified integral presentations can be obtained as special cases of our results. 14 U.K. Saha et al. References [1] L.K. Arora and U.K. Saha, Integrals involving hypergeometric function and H-function, J. Indian Acad. Math., 32(1) (2010), 243-249. [2] C. Fox, The G- and H-functions as symmetrical Fourier kernels, Trans. Amer. Math. Soc., 98(1961), 395-429. [3] A.M. Mathai and R.K. Saxena, The H-Function with Applications in Statistics and Other Disciplines, Wiley Eastern Limited, New Delhi, Bangalore, Bombay, (1978). [4] E.D. Rainville, Special Functions, Chelsea Publication Company, Bronx, New York, (1971). [5] V.P. Saxena, The I-Function, Anamaya Publishers, New Delhi, (2008). [6] H.M. Srivastava, K.C. Gupta and S.P. Goyal, The H-Functions of One and Two Variables with Applications, South Asian Publishers, New Delhi, Madras, (1982).